2015
DOI: 10.1371/journal.pone.0135610
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety in Medical Education: Students’ Perceptions, Knowledge and Attitudes

Abstract: Patient safety is a new and challenging discipline in the Iranian health care industry. Among the challenges for patient safety improvement, education of medical and paramedical students is intimidating. The present study was designed to assess students’ perceptions of patient safety, and their knowledge and attitudes to patient safety education. This cross-sectional analytical study was conducted in 2012 at Urmia University of Medical Sciences, West Azerbaijan province, Iran. 134 students studying medicine, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
80
4
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 19 publications
15
80
4
7
Order By: Relevance
“…This is in close agreement with the result of the study conducted on students of Urmia University (Iran), which reported 32.3% of students think that most errors are due to things that physicians cannot do anything about 23. In contrast to our finding, very low level of agreement over this item is reported in the study done by Leung GK and Patil NG, which showed only 3% of medical students perceive that most errors are due to things that health care professionals cannot do anything about 14…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in close agreement with the result of the study conducted on students of Urmia University (Iran), which reported 32.3% of students think that most errors are due to things that physicians cannot do anything about 23. In contrast to our finding, very low level of agreement over this item is reported in the study done by Leung GK and Patil NG, which showed only 3% of medical students perceive that most errors are due to things that health care professionals cannot do anything about 14…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to this finding, studies conducted in Iran, Pakistan and China reported lower level of disagreement over this issue (19.4%, 33.6% and 46%, respectively) 23,24,14. However, in the current study the presence of more than one-third (41%) students who believe competent health care professionals do not make errors, indicate a fundamental misconception about the nature and pattern of human error 25…”
Section: Discussionmentioning
confidence: 69%
“…Regarding the presence of a formal discipline in the curriculum, although students do not have a discipline on patient safety, most of them showed favorable perceptions of safety, corroborating the results of other studies (4,(6)(7) . Such evidence indicates a cross-thematic approach of the evaluated courses in which teachers, although informally, have been keen to develop the theme.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, establishing formal curriculum in patient safety is essential for training (7) . When performing the analysis of students' responses regarding the conceptual aspects, it became clear that in the affirmative making mistakes in healthcare is inevitable and competent professionals and committed students do not make mistakes that cause harm to patients, there was a higher percentage of discordant responses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 74 ] In relation to knowledge of nursing student about patient safety and patient safety, the majority of them were agree with a knowledge about types of nursing errors, factors contributing to nursing errors, factors influencing patient safety, ways of speaking up about the error and how to report a nursing error while they were neutral with the role of the healthcare institutions such as hospitals in the reporting of errors. These data are in accordance with Nabilou et al (2015) [ 75 ] who compare the perception, knowledge and attitudes between the medical and nursing students' in relation to patient safety and the study revealed that nursing students obtained significantly higher scores on perception towards patient safety than medical students. On the other hand, Edgman-Levitan (2013) and Lorig (2011) [ 76,77 ] argue that patient safety will only improve if the organizational and professional cultures accept the inevitability of error and importance of reporting and learning.…”
Section: Discussionsupporting
confidence: 90%